The use of attractants in the application of food-baits against termites - Zumrat Ganieva; Mukhabbat Khashimova; Kakhraman Rustamov; Voxid Akhmedov (Acta Biologica Sibirica, 2023)
The article presents the results of scientific research on the identification of attractants in the development of food-baits against termites of the genus Anacanthotermes.